Transcranial magnetic stimulation: a historical evaluation and future prognosis of therapeutically relevant ethical concerns. Issue 3 (24th November 2010) - Horvath, Jared C; Perez, Jennifer M; Forrow, Lachlan; Fregni, Felipe; Pascual-Leone, Alvaro
Abstract : Transcranial Magnetic Stimulation (TMS) is a non-invasive neurostimulatory and neuromodulatory technique increasingly used in clinical and research practices around the world. Historically, the ethical considerations guiding the therapeutic practice of TMS were largely concerned with aspects of subject safety in clinical trials. While safety remains of paramount importance, the recent US Food and Drug Administration approval of the Neuronetics NeuroStar TMS device for the treatment of specific medication-resistant depression has raised a number of additional ethical concerns, including marketing, off-label use and technician certification. This article provides an overview of the history of TMS and highlights the ethical questions that are likely arise as the therapeutic use of TMS continues to expand.